Penggunaan Majas dalam Podcast Close The Door di Channel Youtube Deddy Corbuzier - Ghina Mardhatillah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Baturaja, 2023)
The purpose of this research is to describe the most dominant figure of speech and figure of speech contained in the Close the Door podcast on Deddy Corbuzier's YouTube channel. The method used is descriptive qualitative method. The techniques used in collecting data are transcription techniques, listening techniques, and note-taking techniques. Data were analyzed by collecting data, identifying the figure of speech in the conversational speech in the close the door video podcast on Deddy Corbuzier's YouTube channel, classifying, interpreting, and describing the figure of speech contained in the close the door video podcast on Deddy Corbuzier's YouTube channel. The results showed that there are various figures of speech contained in the close the door podcast on Deddy Corbuzier's YouTube channel, including smile 8 figures of speech, metaphor 4 figures of speech, allegory 5 figures of speech, antithesis 4 figures of speech, pleonasm 4 figures of speech, periphrasis 1 figure of speech, anticipation 3 figures of speech , correction 4 figures of speech, hyperbole 5 figures of speech, litotes 5 figures of speech, irony 3 figures of speech, oxymoron 3 figures of speech, zeugma 1 figure of speech, satire 7 figures of speech, innuendo 6 figures of speech, paradox 1 figure of speech, climax 3, anticlimax 2 figures of speech, apostrophe 1 figure of speech, anastrophe 2 figure of speech, apophasis 2 figures of speech, hypelase 3 figures of speech, sarcasm 9 figures of speech, metonymy 7 figures of speech, sinikdoke 10 figures of speech, euphemism 1 figure of speech, antonomasia 15 figures of speech, parallelism 1 figure of speech, ellipsis 2 figures of speech, gradation 2 figures of speech, asyndeton 12 figures of speech, polysendeton 6 figures of speech, alliteration 2 majas, chiasmus 4 majas, epizeukis 11 majas, anaphora 5 majas, epistropha 4 majas, mesodilopsis 1 majas, and epanalepsis 2 majas. The dominant figure of speech in the comparative language style is simile, there are 8 figures of speech, the opposing language style is sarcasm, 9, the linking language style is antonomasia, 15, and the repetition language style, there are 11, epizeukis.